A PC / ABS flame retardant composite material and preparation method thereof
By synergistically using phosphorus, bromine and inorganic flame retardants in PC/ABS flame retardant composite materials, combined with specially treated APP and modified antimony trioxide, the existing flame retardant problems are solved, and the high-efficiency and low-cost flame retardant effect is achieved.
Patent Information
- Application Number
- CN202211499336.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-28
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-11-28
AI Technical Summary
Existing flame retardants have problems such as high toxicity, dripping from combustion, low flame retardant efficiency, and large smoke generation.
The coordinated use of phosphorus-based flame retardants, bromine-based flame retardants and inorganic flame retardants is adopted, combined with specially treated APP and modified antimony trioxide, to improve the compatibility and flame retardant efficiency of the material.
It achieves an efficient flame retardant effect, avoids dripping during combustion, reduces the amount of flame retardant, reduces the preparation cost, and maintains the mechanical properties of the material.
Smart Images

Figure BDA0003966511630000061 
Figure BDA0003966511630000071 
Figure BDA0003966511630000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and particularly relates to a PC / ABS flame retardant composite material and a preparation method thereof. Background Art
[0002] With the rapid development of the national economy, the application fields of engineering plastics are becoming wider and wider. PC / ABS alloy is a widely used engineering plastic, mainly used in automotive internal parts, business machines, communication equipment, household appliances and lighting equipment. In some fields, especially in electronic and electrical equipment, the requirements for the flame retardant properties of its materials are particularly strict. In addition, in order to maintain the practicality of the material, it is not only required to meet the corresponding flame retardant requirements, but also have excellent mechanical properties, aging resistance, environmental protection and other characteristics.
[0003] Brominated flame retardants are still widely used in the field of PC / ABS flame retardant composite materials due to their high flame retardant efficiency and low cost. Among them, tetrabromobisphenol A and decabromodiphenylethane are widely used in the field of PC / ABS flame retardant, mainly due to their high flame retardancy. They can achieve a high flame retardant level at a low addition amount. They do not produce toxic polybrominated dibenzodioxane (DBDO) and polybrominated dibenzofuran (DBDF) during thermal decomposition or combustion, and do not cause harm to the environment. The thermoplastics flame-retarded by them can be recycled. However, the materials flame-retarded by brominated flame retardants produce a large amount of smoke during combustion, and are prone to produce a large amount of toxic and harmful gases during the combustion process. In North America and Europe and other countries, policies have been issued to limit the use of brominated flame retardants. Therefore, it is of great significance to study the preparation of high-efficiency multi-flame retardants and synergistic brominated flame retardants for use in PC / ABS flame retardant composite materials.
[0004] The Chinese patent document "A flame-retardant PC / ABS alloy for automotive interior parts and its preparation method (patent application number: 201210076280.5)" discloses a flame-retardant PC / ABS alloy for automotive interior parts, including the following components by weight: 50 parts of ABS resin, 40-60 parts of PC resin, 0.5-1.5 parts of polytetrafluoroethylene, 20-50 parts of composite flame retardant, and further, the composite flame retardant is composed of the following components by weight: 100 parts of decabromodiphenylethane, 20-30 parts of tris(2-chloropropyl) phosphate, 10-20 parts of melamine cyanurate, and 10-30 parts of magnesium hydroxide. The invention has low production cost, good processing performance, high flame retardant level and is environmentally friendly. The flame-retardant PC / ABS alloy for automotive interior parts of the invention is particularly suitable for injection molding into various automotive interior parts, but it requires a large number of composite flame retardants to make the material have good flame retardancy, which is costly and affects the mechanical properties of the flame retardant material.
[0005] The Chinese patent document "An impact-resistant halogen-free flame-retardant PC / ABS blend alloy and its preparation method (patent application number: 202010035179.X)" discloses an impact-resistant halogen-free flame-retardant PC / ABS blend alloy, which includes the following components by weight: PC: 30-72 parts, ABS: 5-32 parts, epoxy-terminated modified polysiloxane: 0.1-10 parts, compatibilizer: 1-10 parts, toughening agent: 1-15 parts, transesterification catalyst: 0.01-0.5 parts, sulfonate flame retardant: 0-1 parts, anti-dripping agent: 0-2 parts, antioxidant: 0-1 parts, lubricant: 0-1 parts. The invention improves the flame retardant properties of the blend alloy by adding epoxy-terminated modified polysiloxane and transesterification catalyst, which can effectively reduce the amount of flame retardant. However, the invention patent has poor flame retardant inhibition performance and is prone to produce a large amount of toxic and harmful gases during combustion.
[0006] It is a trend to develop new flame retardant materials that have the advantages of all existing flame retardants, such as low smoke volume, good and stable thermal and mechanical properties, no dripping during combustion, and little environmental pollution. Summary of the invention
[0007] The purpose of the present invention is to overcome the problems of existing flame retardants such as high toxicity, dripping during combustion, low flame retardant efficiency, large smoke generation, etc., and to provide a PC / ABS flame retardant composite material and a preparation method thereof. The present invention is based on PC / ABS as a base resin, and phosphorus flame retardants, bromine flame retardants, and inorganic flame retardants are added. While integrating the advantages of these three types of flame retardants, the flame retardant efficiency is high and no dripping occurs when the material burns.
[0008] In order to achieve the above technical objectives, the technical solution of the present invention is:
[0009] A PC / ABS flame retardant composite material, comprising the following raw materials in parts by weight:
[0010] A is the base resin: PC and ABS, 100 parts;
[0011] B is a phosphorus flame retardant, 3 to 8 parts;
[0012] C is a brominated flame retardant, 8 to 15 parts;
[0013] D is an inorganic flame retardant, 6 to 10 parts;
[0014] E is other additives, 0.6 to 2 parts.
[0015] Preferably, the weight ratio of PC to ABS is 1 to 3:1.
[0016] Preferably, the phosphorus-based flame retardant is DOPO-M-APP.
[0017] Preferably, the method for preparing DOPO-M-APP comprises the following steps:
[0018] S1: In units of parts by weight, 50 parts of APP were added to an organic solvent with a solid-liquid ratio of 1:3.5, and the temperature was controlled to rise to 60°C and stirred to obtain a mixed solution. 30 mL of a titanate coupling agent was added to the mixed solution, the temperature was kept constant, stirring was continued for 20 min, and the mixture was heated to 100°C and reacted for 4 h. After the reaction was completed, the mixture was filtered and the obtained block was placed in an oven and dried at 105°C for 6 h to obtain M-APP;
[0019] S2: Add 50 parts by weight of M-APP to an organic solvent at a solid-liquid ratio of 1:3.5, heat to 60°C, and stir for 15 minutes to prepare an M-APP solution;
[0020] S3: In parts by weight, add 10 parts of DOPO ground into powder to the M-APP solution obtained in step S2, stir and heat to 100°C, react for 3 hours, and after the reaction is completed, cool to room temperature, filter, wash with ethanol 3 times, and dry at 105°C for 6 hours to obtain DOPO-M-APP.
[0021] Preferably, the organic solvent in step S1 and step S2 is ethanol.
[0022] Preferably, the brominated flame retardant is tetrabromobisphenol A or decabromodiphenylethane.
[0023] Preferably, the inorganic flame retardant includes 3 to 5 parts of modified antimony trioxide M-Sb2O3 and 3 to 5 parts of calcium-based bentonite.
[0024] Preferably, the preparation method of the modified antimony trioxide M-Sb2O3 comprises the following steps:
[0025] Antimony trioxide is put into a mixer, and then vinyl tributylacetonate silane is added, the mass ratio of the antimony trioxide to the vinyl tributylacetonate silane is 100:1.5-3, and the mixture is stirred for modification for 8-15 minutes at a temperature of 90-120°C and a rotation speed of 1500-3000 r / min to obtain modified antimony trioxide M-Sb2O3.
[0026] Preferably, the other additives include 0.5 to 1.5 parts of lubricant and 0.1 to 0.5 parts of anti-dripping agent.
[0027] The present invention also provides a method for preparing a PC / ABS flame retardant composite material, comprising the following steps:
[0028] (1) Drying of raw materials: weigh the raw materials according to the proportion, and then place the raw materials in a forced air drying oven for 1 to 3 hours at a temperature of 105 to 140°C;
[0029] (2) Mixing the raw materials: Place the dried raw materials in a high-speed mixer and heat and mix them evenly, wherein the temperature is controlled at 60-100°C, the mixing time is 5-30 minutes, and the speed is 1000-2000 r / min;
[0030] (3) Processing and extrusion: adding the mixed raw materials into a twin-screw extruder for processing and extrusion, the extruder temperature is controlled at 220-250°C, the die head is 230-250°C, the screw speed is controlled at 300-600r / min, and the pressure is 1.0-3.0MPa for melt extrusion;
[0031] (4) Injection molding: The extruded product is injection molded by an injection molding machine with an injection pressure of 0.5-1 MPa, an injection barrel temperature of 230-250°C, and a mold temperature of 30-40°C.
[0032] Compared with the prior art, the advantages of the present invention are as follows:
[0033] 1. The present invention will be used in PC / ABS flame-retardant composite materials to obtain good flame-retardant synergistic effects, and maintain the thermal stability and mechanical properties of the composite materials, thereby preparing flame-retardant composite materials with excellent properties;
[0034] 2. The present invention uses phosphorus flame retardants, bromine flame retardants and inorganic flame retardants in a coordinated manner in the PC / ABS flame retardant composite material, thereby reducing the amount of flame retardants used and the cost of preparing the flame retardant composite material;
[0035] 3. The present invention uses specially treated APP and modified antimony trioxide in the PC / ABS flame retardant composite material, which improves the compatibility of the material and has less negative impact on the mechanical properties of the material. Specific embodiments
[0036] The present invention is illustrated by the following examples, but the scope of the invention is not limited thereto.
[0037] In the embodiment of the present invention, the PC / ABS flame retardant composite material comprises the following raw materials in parts by weight:
[0038] A is a base resin: PC and ABS, 100 parts, the weight ratio of PC to ABS is 1 to 3:1;
[0039] B is a phosphorus flame retardant: DOPO-M-APP, 3 to 8 parts;
[0040] C is a brominated flame retardant: tetrabromobisphenol A or decabromodiphenylethane, 8 to 15 parts;
[0041] D is an inorganic flame retardant: modified antimony trioxide M-Sb2O3, 3 to 5 parts; calcium-based bentonite, 3 to 5 parts;
[0042] E is other additives: 0.5-1.5 parts of lubricant and 0.1-0.5 parts of anti-dripping agent.
[0043] The technical principle of the present invention is as follows: ammonium polyphosphate (APP) is an inorganic phosphorus flame retardant with high phosphorus and nitrogen content and low cost. When the polymer burns, it can release non-flammable ammonia in the gas phase to reduce the concentration of gases such as oxygen during the combustion process; it decomposes in the condensed phase to generate phosphoric acid as a strong dehydrating agent, promotes the dehydration and carbonization of the polymer to form a carbon layer, isolates oxygen and exerts a flame retardant effect, and is widely used in PE, PBT, PC / ABS plastics. However, APP is easy to absorb moisture, has poor compatibility with polymer materials, and is easy to precipitate. Therefore, APP needs to be modified to reduce its hygroscopicity, increase its compatibility with polymers, and then improve the flame retardant properties of the polymer and reduce the influence of APP on the mechanical properties of polymer materials. The present invention uses a coupling agent to modify ammonium polyphosphate to improve the interface properties of inorganic substances, and introduces DOPO as a carbon source in a grafting manner to form a carbon layer, thereby well solving the shortcomings of low flame retardant efficiency, poor anti-melting droplet property, and difficulty in carbonization during the combustion process of PC / ABS resin.
[0044] Inorganic flame retardants such as antimony trioxide have good flame retardant synergy, and have been proven to have good flame retardant effects when used in conjunction with brominated flame retardants. However, antimony trioxide is an inorganic powder, and its compatibility with PC / ABS resin is still poor. Therefore, antimony trioxide modified with a coupling agent has good compatibility when used in flame retardant materials, and can also improve flame retardant synergy and reduce the impact on the mechanical properties of flame retardant composite materials. The patent of the present invention uses vinyl tributylidene oxime silane to modify antimony trioxide, and effectively improves the interface performance of the two through the interaction between the chemical bonds between the vinyl and carbonate.
[0045] Calcium-based bentonite: It is a new type of inorganic functional material with a layered structure. When bentonite is heated, its structural hydrated layer hydroxyl and interlayer ions are released in the form of water and CO2, which reduces the concentration of combustion gas and blocks the flame retardant effect of O2. The structural hydrated layer hydroxyl and interlayer ions of bentonite are separated from the layer at different temperatures, so that flame retardants can be released in a relatively low range (200-800℃). In the flame retardant process, it absorbs a large amount of heat, which is conducive to reducing the high temperature generated during combustion.
[0046] A flame retardant composite material with excellent properties is prepared by using phosphorus flame retardants, bromine flame retardants and inorganic flame retardants to synergistically flame retard PC / ABS flame retardant composite materials.
[0047] In an embodiment of the present invention, the method for preparing DOPO-M-APP comprises the following steps:
[0048] S1: In units of parts by weight, 50 parts of APP were added to anhydrous ethanol with a solid-liquid ratio of 1:3.5, and the temperature was controlled to rise to 60°C and stirred to obtain a mixed solution. 30 mL of titanate coupling agent was added to the mixed solution, the temperature was kept constant, stirring was continued for 20 min, and the mixture was heated to 100°C and reacted for 4 h. After the reaction was completed, the mixture was filtered and the obtained block was placed in an oven and dried at 105°C for 6 h to obtain M-APP;
[0049] S2: Add 50 parts of M-APP to anhydrous ethanol in parts by weight at a solid-liquid ratio of 1:3.5, heat to 60°C, and stir for 15 minutes to prepare an M-APP solution;
[0050] S3: In parts by weight, add 10 parts of DOPO ground into powder to the M-APP solution obtained in step S2, stir and heat to 100°C, react for 3 hours, and after the reaction is completed, cool to room temperature, filter, wash with anhydrous ethanol for 3 times, and dry at 105°C for 6 hours to obtain DOPO-M-APP.
[0051] The preparation method of the modified antimony trioxide M-Sb2O3 comprises the following steps:
[0052] Antimony trioxide is put into a mixer, and then vinyl tributylacetonate silane is added, the mass ratio of the antimony trioxide to the vinyl tributylacetonate silane is 100:1.5-3, and the mixture is stirred for modification for 8-15 minutes at a temperature of 90-120°C and a rotation speed of 1500-3000 r / min to obtain modified antimony trioxide M-Sb2O3.
[0053] The preparation method of the PC / ABS flame retardant composite material comprises the following steps:
[0054] (1) Drying of raw materials: weigh the raw materials according to the proportion, and then place the raw materials in a forced air drying oven for 1 to 3 hours at a temperature of 105 to 140°C;
[0055] (2) Mixing the raw materials: Place the dried raw materials in a high-speed mixer and heat and mix them evenly, wherein the temperature is controlled at 60-100°C, the mixing time is 5-30 minutes, and the speed is 1000-2000 r / min;
[0056] (3) Processing and extrusion: adding the mixed raw materials into a twin-screw extruder for processing and extrusion, the extruder temperature is controlled at 220-250°C, the die head is 230-250°C, the screw speed is controlled at 300-600r / min, and the pressure is 1.0-3.0MPa for melt extrusion;
[0057] (4) Injection molding: The extruded product is injection molded by an injection molding machine with an injection pressure of 0.5-1 MPa, an injection barrel temperature of 230-250°C, and a mold temperature of 30-40°C.
[0058] The following is explained with more specific examples.
[0059] Example 1
[0060] (1) Raw material formula for preparing PC / ABS flame retardant composite materials: (all in parts by weight)
[0061]
[0062]
[0063] (2) Preparation method of PC / ABS flame retardant composite material:
[0064] a. Raw material drying: weigh the raw materials according to the above ratio, and then place the raw materials in a blast drying oven for 1 hour, and the temperature is controlled at 105°C;
[0065] b. Raw material mixing: Place the dried raw materials in a high-speed mixer and heat and mix them evenly. The temperature is controlled at 60-80°C and the mixing time is 10 minutes.
[0066] c. Processing and extrusion: Add the mixed raw materials into a twin-screw extruder for processing and extrusion. The extruder temperature is controlled at 230-250°C, the die head is 230°C, the screw speed is controlled at 300r / min, and the pressure is 1.0-3.0MPa for melt extrusion;
[0067] d. Injection molding: The extruded product is injection molded by an injection molding machine to obtain a PC / ABS flame retardant composite material, wherein the injection pressure is 0.5 MPa, the injection barrel temperature is 230°C, the mold temperature is 40°C, the mold closing time is 30s, and the injection time is 10s.
[0068] In this embodiment, the preparation method of DOPO-M-APP comprises the following steps:
[0069] S1: In units of parts by weight, 50 parts of APP were added to anhydrous ethanol with a solid-liquid ratio of 1:3.5, and the temperature was controlled to rise to 60°C and stirred to obtain a mixed solution. 30 mL of titanate coupling agent was added to the mixed solution, the temperature was kept constant, stirring was continued for 20 min, and the mixture was heated to 100°C and reacted for 4 h. After the reaction was completed, the mixture was filtered and the obtained block was placed in an oven and dried at 105°C for 6 h to obtain M-APP;
[0070] S2: Add 50 parts of M-APP to anhydrous ethanol in parts by weight at a solid-liquid ratio of 1:3.5, heat to 60°C, and stir for 15 minutes to prepare an M-APP solution;
[0071] S3: In parts by weight, add 10 parts of DOPO ground into powder to the M-APP solution obtained in step S2, stir and heat to 100°C, react for 3 hours, and after the reaction is completed, cool to room temperature, filter, wash with anhydrous ethanol for 3 times, and dry at 105°C for 6 hours to obtain DOPO-M-APP.
[0072] The preparation method of the modified antimony trioxide M-Sb2O3 comprises the following steps:
[0073] Antimony trioxide was put into a mixer, and then vinyltributylacetonate silane was added, the mass ratio of antimony trioxide to vinyltributylacetonate silane was 100:1.5, and the mixture was stirred for modification for 10 minutes at a temperature of 100°C and a rotation speed of 2000 r / min to obtain modified antimony trioxide M-Sb2O3.
[0074] (3) The flame retardant and mechanical properties of the product are tested. The results are shown in the following table:
[0075] name Pure PC / ABS performance Example 1 Adoption of standards Limiting oxygen index / % 18.2 27.9 GB / T 2406-2009 Vertical burning level No level V-0@3.2mm GB / T 2408-2021 Smoke Density Rating SDR 86 74 GB8627-2007 Tensile strength / Mpa 45 55 GB / T 1040.2-2006
[0076] Note: Pure PC / ABS is only a mixture of two resins, and no other materials are added.
[0077] As can be seen from the above table, compared with the performance of pure PC / ABS, after adding the composite flame retardant and processing aid, the limiting oxygen index of the flame retardant material in Example 1 reaches 27.9%, the vertical burning grade can reach V-0@3.2mm, the smoke density grade SDR reaches 74, and the tensile strength is 55Mpa, which has good flame retardant properties and maintains good mechanical properties.
[0078] Example 2
[0079] (1) Raw material formula for preparing PC / ABS flame retardant composite materials: (all in parts by weight)
[0080] Raw material components Servings / phr Polycarbonate (PC) 75 Acrylonitrile Butadiene Styrene (ABS) 25 DOPO-M-APP 8 Tetrabromobisphenol A 9 <![CDATA[Modified antimony trioxide (M-Sb2O3)]]> 3 Calcium Bentonite 3 Lubricant (ethylene bisstearamide) 0.5 Anti-drip agent (PTFE) 0.2
[0081] (2) Preparation method of PC / ABS flame retardant composite material: except for the different raw material formula, the other methods are basically the same as those in Example 1.
[0082] (3) The flame retardant and mechanical properties of the product are tested. The results are shown in the following table:
[0083]
[0084]
[0085] As can be seen from the above table, compared with the performance of pure PC / ABS, after adding the composite flame retardant and processing aid, the flame retardant material of Example 2 has a limiting oxygen index of 28.2%, a vertical combustion rating of V-0@3.2mm, a smoke density rating of SDR of 72, and a tensile strength of 53Mpa, which has good flame retardant properties and maintains good mechanical properties. Compared with Example 1, after adding DOPO-M-APP, the limiting oxygen index and smoke density level of Example 2 are improved, indicating that DOPO-M-APP has good flame retardant synergy, which is mainly due to the fact that the phosphorus-based flame retardant contains PN flame retardant elements, which form a carbon layer in the condensed phase during combustion, isolating the combustible from the air and playing a flame retardant role.
[0086] Example 3
[0087] (1) Raw material formula for preparing PC / ABS flame retardant composite materials: (all in parts by weight)
[0088] Raw material components Servings / phr Polycarbonate (PC) 75 Acrylonitrile Butadiene Styrene (ABS) 25 DOPO-M-APP 8 Tetrabromobisphenol A 12 <![CDATA[Modified antimony trioxide (M-Sb2O3)]]> 4 Calcium Bentonite 3 Lubricant (ethylene bisstearamide) 0.5 Anti-drip agent (PTFE) 0.2
[0089] (2) Preparation method of PC / ABS flame retardant composite material: except for the different raw material formula, the other methods are basically the same as those in Example 1.
[0090] (3) The flame retardant and mechanical properties of the product are tested. The results are shown in the following table:
[0091]
[0092]
[0093] As can be seen from the above table, compared with the performance of pure PC / ABS, after adding the composite flame retardant and processing aid, the limiting oxygen index of the flame retardant material in Example 3 reaches 28.9%, the vertical burning grade can reach V-0@3.2mm, the smoke density grade SDR reaches 74, and the tensile strength is 58Mpa, which has good flame retardant properties and maintains good mechanical properties. Compared with Example 2, after adding tetrabromobisphenol A and modified antimony trioxide, the limiting oxygen index and smoke density grade of Example 3 are improved, indicating that tetrabromobisphenol A and modified antimony trioxide have good flame retardancy, which is mainly due to the bromine antimony flame retardant containing flame retardant elements, which can capture combustion free radicals in the gas phase when burning, and dilute the air to play a flame retardant role.
[0094] Comparative Example 1
[0095] (1) Raw material formula for composite material preparation: (all in parts by weight)
[0096] Raw material components Servings / phr Polycarbonate (PC) 75 Acrylonitrile Butadiene Styrene (ABS) 25 DOPO-M-APP 0 Tetrabromobisphenol A 9 <![CDATA[Modified Antimony Trioxide (M-Sb2O3)]]> 3 Calcium Bentonite 3 Lubricant (ethylene bisstearamide) 0.5 Anti-drip agent (PTFE) 0.2
[0097] (2) Preparation method of PC / ABS flame retardant composite material: except for the different raw material formula, the other methods are basically the same as those in Example 1.
[0098] (3) The flame retardant and mechanical properties of the product are tested. The results are shown in the following table:
[0099]
[0100]
[0101] As can be seen from the above table, the limiting oxygen index of the flame retardant material prepared in Comparative Example 1 reaches 26.8%, the vertical combustion level can reach V-1@3.2mm, the smoke density level SDR reaches 89, and the tensile strength is 52Mpa. Compared with Example 1, Comparative Example 1 does not add DOPO-M-APP, and its limiting oxygen index and smoke density level are reduced, indicating that the addition of DOPO-M-APP has good flame retardancy. This is mainly because the phosphorus-based flame retardant DOPO-M-APP contains PN flame retardant elements, which form a carbon layer in the condensed phase when burning, isolating the combustible from the air and playing a flame retardant role.
[0102] Comparative Example 2
[0103] (1) Raw material formula for composite material preparation: (all in parts by weight)
[0104] Raw material components Servings / phr Polycarbonate (PC) 75 Acrylonitrile Butadiene Styrene (ABS) 25 DOPO-M-APP 3 Tetrabromobisphenol A 9 <![CDATA[Modified antimony trioxide (M-Sb2O3)]]> 3 Calcium Bentonite 0 Lubricant (ethylene bisstearamide) 0.5 Anti-drip agent (PTFE) 0.2
[0105] (2) Preparation method of PC / ABS flame retardant composite material: except for the different raw material formula, the other methods are basically the same as those in Example 1.
[0106] (3) The flame retardant and mechanical properties of the product are tested. The results are shown in the following table:
[0107]
[0108]
[0109] As can be seen from the above table, the flame retardant material prepared in Comparative Example 2 has a limiting oxygen index of 26.4%, a vertical combustion rating of V-1@3.2mm, a smoke density rating SDR of 92, and a tensile strength of 51Mpa. Compared with Example 1, Comparative Example 2 does not add calcium-based bentonite, and its limiting oxygen index and smoke density rating are reduced, indicating that the addition of calcium-based bentonite has good flame retardancy. This is mainly because calcium-based bentonite has a layered structure, and when burning, it can form a layered material in the condensed phase stage, which plays a role in blocking air, thereby playing a flame retardant synergistic role.
[0110] Comparative Example 3
[0111] (1) Raw material formula for composite material preparation: (all in parts by weight)
[0112] Raw material components Servings / phr Polycarbonate (PC) 75 Acrylonitrile Butadiene Styrene (ABS) 25 DOPO-M-APP 3 Tetrabromobisphenol A 9 <![CDATA[Antimony trioxide (Sb2O3)]]> 3 Calcium Bentonite 3 Lubricant (ethylene bisstearamide) 0.5 Anti-drip agent (PTFE) 0.2
[0113] (2) Preparation method of PC / ABS flame retardant composite material: except for the different raw material formula, the other methods are basically the same as those in Example 1.
[0114] (3) The flame retardant and mechanical properties of the product are tested. The results are shown in the following table:
[0115]
[0116]
[0117] As can be seen from the above table, the flame retardant material obtained in Comparative Example 3 has a limiting oxygen index of 26.9%, a vertical combustion rating of V-0@3.2mm, a smoke density rating of SDR of 78, and a tensile strength of 53Mpa. Compared with Example 1, Comparative Example 3 adds unmodified antimony trioxide, and its limiting oxygen index and smoke density rating are reduced, indicating that the addition of antimony trioxide has good flame retardancy after modification. This is mainly because antimony trioxide is an inorganic powder, and its interface compatibility and dispersibility with the polymer matrix are poor, which affects its reaction degree with the brominated flame retardant, and then it plays a flame retardant synergistic role, and finally shows that the flame retardant synergistic effect is poor.
[0118] Although the above describes the specific implementation methods of the present invention, it is not intended to limit the scope of protection of the invention. Those skilled in the art should understand that, based on the technical solution of the present invention, various modifications or variations that can be made by those skilled in the art without creative work are still within the scope of protection of the present invention.
Claims
1. A PC / ABS flame retardant composite material, characterized in that: The unit is weight parts, including the following raw materials: A is the base resin: PC and ABS, 100 parts; B is a phosphorus flame retardant, 3 to 8 parts; C is a brominated flame retardant, 8 to 15 parts; D is an inorganic flame retardant, 6 to 10 parts; E is other additives, 0.6-2 parts; The weight ratio of PC to ABS is 1 to 3:1; The other additives include 0.5 to 1.5 parts of lubricant and 0.1 to 0.5 parts of anti-dripping agent; The phosphorus-based flame retardant is DOPO-M-APP, and the preparation method of the DOPO-M-APP comprises the following steps: S1: In units of parts by weight, 50 parts of APP were added to an organic solvent with a solid-liquid ratio of 1:3.5, and the temperature was controlled to rise to 60°C and stirred to obtain a mixed solution. 30 mL of a titanate coupling agent was added to the mixed solution, the temperature was kept constant, stirring was continued for 20 min, and the mixture was heated to 100°C and reacted for 4 h. After the reaction was completed, the mixture was filtered and the obtained block was placed in an oven and dried at 105°C for 6 h to obtain M-APP; S2: Add 50 parts by weight of M-APP to an organic solvent at a solid-liquid ratio of 1:3.5, heat to 60°C, and stir for 15 minutes to prepare an M-APP solution; S3: In units of parts by weight, 10 parts of DOPO ground into powder are added to the M-APP solution prepared in step S2, stirred and heated to 100°C, reacted for 3 hours, and after the reaction is completed, cooled to room temperature, filtered, washed with ethanol for 3 times, and dried at 105°C for 6 hours to obtain DOPO-M-APP; The inorganic flame retardant includes 3 to 5 parts of modified antimony trioxide M-Sb2O3 and 3 to 5 parts of calcium-based bentonite; The preparation method of the modified antimony trioxide M-Sb2O3 comprises the following steps: Put antimony trioxide into a mixer, then add vinyl tributylacetonate oxime silane, the mass ratio of antimony trioxide to vinyl tributylacetonate oxime silane is 100:1.5-3, stir and modify for 8-15 minutes at a temperature of 90-120° C. and a rotation speed of 1500-3000 r / min to obtain modified antimony trioxide M-Sb2O3; The method for preparing the PC / ABS flame retardant composite material is characterized by comprising the following steps: (1) Drying of raw materials: weigh the raw materials according to the proportion, and then place the raw materials in a forced air drying oven for 1 to 3 hours at a temperature of 105 to 140°C; (2) Mixing the raw materials: Place the dried raw materials in a high-speed mixer and heat and mix them evenly, wherein the temperature is controlled at 60-100°C, the mixing time is 5-30 minutes, and the speed is 1000-2000 r / min; (3) Processing and extrusion: adding the mixed raw materials into a twin-screw extruder for processing and extrusion, the extruder temperature is controlled at 220-250°C, the die head is 230-250°C, the screw speed is controlled at 300-600r / min, and the pressure is 1.0-3.0MPa for melt extrusion; (4) Injection molding: The extruded product is injection molded by an injection molding machine with an injection pressure of 0.5-1 MPa, an injection barrel temperature of 230-250°C, and a mold temperature of 30-40°C.
2. The PC / ABS flame retardant composite material according to claim 1, characterized in that: The organic solvent in step S1 and step S2 is ethanol.
3. The PC / ABS flame retardant composite material according to claim 1, characterized in that: The brominated flame retardant is tetrabromobisphenol A or decabromodiphenylethane.
4. A method for preparing the PC / ABS flame retardant composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Drying of raw materials: weigh the raw materials according to the proportion, and then place the raw materials in a forced air drying oven for 1 to 3 hours at a temperature of 105 to 140°C; (2) Mixing the raw materials: Place the dried raw materials in a high-speed mixer and heat and mix them evenly, wherein the temperature is controlled at 60-100°C, the mixing time is 5-30 minutes, and the speed is 1000-2000 r / min; (3) Processing and extrusion: adding the mixed raw materials into a twin-screw extruder for processing and extrusion, the extruder temperature is controlled at 220-250°C, the die head is 230-250°C, the screw speed is controlled at 300-600r / min, and the pressure is 1.0-3.0MPa for melt extrusion; (4) Injection molding: The extruded product is injection molded by an injection molding machine with an injection pressure of 0.5-1 MPa, an injection barrel temperature of 230-250°C, and a mold temperature of 30-40°C.
Citation Information
Patent Citations
Flame-retardant PC / ABS (Poly Carbonate / Acrylonitrile Butadiene Styrene) plastic for automobile interior and preparation method thereof
CN102604359A
Impact-resistant halogen-free flame-retardant PC / ABS blend alloy and preparation method thereof
CN111138824A
LDPE (Low-Density Polyethylene) / EVA (Ethylene Vinyl Acetate Copolymer) anti-flaming material and preparation method thereof
CN102643469A
Flame retardant for high density polyethylene
CN104311967A
Novel flame retardant based on APP and DOPO and preparation method of novel flame retardant
CN113045800A